MODELLING BUILDING FAÇADE INFLUENCE ON SOUND FIELD FORMATION - Шевченко, Ю.; Береговий, О.; Паращанов, В. (Proceedings of National Aviation University (archive), 2012)
The issue of proper ways to calculate the influence of building façade on sound field formation in citystreets is studied. In the article two ray models of sound reflection from different impedance surfaces are developed and investigated: classical ray model and ray model, which takes into account autocorrelationfunction for rays for broadband noise source. Results verification has been done by comparison with data,obtained experimentally, and results of numerical calculation by finite elements method. Accuracy of resultsfor surfaces with different impedance characteristics has been analyzed. The feasibility of using analyticaland numerical models for a certain frequencies range has been considered